A Compariosn of efficacy of insecticide-Treated and Untreated Bednets in Preventing Malaria in Gambian Children - D'Alessandro, U.; Olaleye, B. O.; McGuire, W.; Thomson, M. C.; Langerock, P.; Bennett, S.; Greenwood, B. M. (Oxford University Press)
An evaluation of the Gambian national insecticide impregnated bed net programme, which has introduced insecticide treatment of bed nets into all primary health care (PHC) villages in The Gambia, provided an opportunity to compare the individual risk of malaria in children who slept under untreated or insecticide-treated bed nets. 2300 children 1–4 years old were selected for a survey at the end of the 1992 rainy season, 1500 from PHC villages and 800 from non-PHC villages. All malariometric indices were lower, and the mean packed cell volume was higher, in children who slept regularly under treated or untreated bed nets than in those who did not use a net. This study suggested that untreated bed nets provide some individual protection against malaria, although not as efficiently as that provided by insecticide-treated bed nets which were particularly effective at preventing infections accompanied by high parasitaemia.
Oxford University Press (OUP) has partnered with Copyright Clearance Center's RightsLink service to offer a variety of options for reusing this content.
Keywords: Malaria; Prevention; Bed-nets; Insecticide-treatment; The Gambia child; Insecticide treatment; Primary health care; Infections